Nebulized antibiotics in mechanically ventilated patients: roadmap and challenges. Issue 3 (4th March 2017) - Poulakou, G; Siakallis, G; Tsiodras, S; Arfaras-Melainis, A; Dimopoulos, G
ABSTRACT: Introduction : Nebulized antibiotics use has become common practice in the therapeutics of pneumonia in cystic fibrosis patients. There is an increasing interest in their use for respiratory infections in mechanically ventilated (MV) patients in order to a) overcome pharmacokinetic issues in the lung compartment with traditional systemic antibiotic use and b) prevent the emergence of multi-drug-resistant (MDR) pathogens. Areas covered : The beneficial effects of antibiotic nebulization in MV patients e.g. increasing efficacy, reduced toxicity and prevention of resistance are described. Physicochemical parameters of optimal lung deposition, characteristics of currently available nebulizers, practical aspects of the procedure, including drug preparation and adjustments of ventilator and circuit parameter are presented. Antibiotics used in nebulized route, along with efficacy in various clinical indications and safety issues are reviewed. Expert commentary : The safety of nebulization of antibiotics has been proven in numerous studies; efficacy as adjunctive treatment to intravenous regimens or as monotherapy has been demonstrated in ventilator-associated pneumonia or ventilator-associated tracheobronchitis due to MDR or susceptible pathogens. However, due to the heterogeneity of studies, multiple meta-analyses fail to demonstrate a clear effect. Clarification of indications, standardization of technique and implementation of clinical practice guidelines, based on new large-scale trials will lead to the optimal use of nebulized antibiotics.